Desenvolvimento de software de visão computacional para avaliação do perfil de jatos oriundos de bicos injetores diesel common rail - Moreira Filho, Antônio Adalberto Cavalcante (2018)
Atomization is a process of high relevance in the combustion efficiency in a diesel cycle engine and in the emission of pollutant and particulate matter. In order to meet vehicle emission standards, new technologies have been developed, among them is the common rail injection system. The reduction of the sulfur content in petroleum diesel and the addition of biodiesel caused problems in the element responsible for the atomization of fuel in the combustion chamber: the injector nozzle. This way, the aim of the present work is to investigate the parameters of cone angle, penetration and tip velocity, which are possible to be visualized with the direct capture technique, and to correlate them with the integrity of the nozzle in its new and after-test conditions. An image processing software was developed, and images were captured using a high-speed CCD camera i-SPEED 3 for the evaluation of the atomized jet profile. The injector nozzles were tested with different fuels on a TM 507-III bench for a period of 60 h. A correlation between the nozzle needle assembly and its flow rates was observed, as well as differences in the homogeneity of the jets after the tests, evidenced by the surface condition of the holes.